A note on how well available income information identifies low-income students - Gordon Winston; Catharine Hill; David Zimmerman (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2007)
This note looks at the quality of the information on family income that selective colleges rely on to increase equality of opportunity by recruiting high-ability, low-income students. Individual family income estimates embedded in the College Board's search parameters are compared, for 635 recent Williams matriculants, with their incomes as reported on IRS Forms 1040 and, for further comparison, with self-reported incomes. The data suggest that there is considerable room for improvement and, indeed, until there is better information, that any effort to increase equality of opportunity by energetic recruitment of high-ability, low-income students will be haphazard at best.
Keywords: 330